EXPANSION OF THE BUSINESS SECTOR (Web of Teachers: Inderscience Research, 2025)
This article covers the expansion of the business sector on the basis of issues of development of small and medium-sized businesses in Uzbekistan, as a result of measures aimed at creating economic reforms and a favorable business environment in the country, new opportunities for business activities are being opened.